Carboxyhemoglobin Does Not Predict the Need of Mechanical Ventilation and Prognosis during COPD Exacerbation - Shimon Izhakian; Eitan Harper; Oleg Gorelik; Assaf Frajman; Ori Mekiten; Adina Bar-Chaim; Mordechai Reuven Kramer (Canadian Respiratory Journal)
Background. Carboxyhemoglobin (COHb) is a complex formed by the binding of carbon monoxide to hemoglobin in blood. Higher COHb levels have been associated with poor prognosis in a variety of pulmonary disorders. However, little is known regarding the prognostic significance of COHb among individuals with chronic obstructive pulmonary disease (COPD) exacerbation. Methods. In a retrospective study, we evaluated associations of venous COHb levels on hospital admission with the need for invasive mechanical ventilation, in-hospital mortality, and rehospitalization, among 300 patients hospitalized for COPD exacerbation in internal medical wards. Results. Rates of in-hospital death and 1-year recurrent hospitalizations were 11.0% and 59.6%, respectively. COHb levels were not significantly associated with in-hospital mortality (OR = 0.82, P=0.25, 95% CI 0.59–1.15) or with 1-year rehospitalizations (OR = 0.91, P=0.18, 95% CI 0.79–1.04). The mean COHb level did not differ significantly between patients who needed invasive mechanical ventilation and those who were not invasively mechanically ventilated during the current hospitalization (2.01 ± 1.42% vs. 2.19 ± 1.68%, P=0.49). Conclusions. Among patients hospitalized with COPD exacerbation in internal medicine wards, COHb levels on admission were not associated with invasive mechanical ventilation treatment, rehospitalizations, or mortality.